Hydraulic fracturing considerations: Insights from analogue models, and its viability in Colombia - Dilan Arturo Martínez-Sánchez; Giovanny Jiménez Díaz (Earth Sciences Research Journal)
Fracking is being considered around the world as a potential method in the hydrocarbons extraction given the increase of production in USA and Canada during the last years with its implementation. The most criticized feature of the technique of fracking is the contamination of underground waters by fluids connected through the generated and/or pre-existing fractures. This work evaluates the viability of fracking in Colombian territory based in the study of the analogue models, considering the elastic properties of the reservoir rocks using gelatin, sand and clay that apply scaled pressure (lithostatic pressure to scale). The gelatin is used to simulate the reservoir zone, the clay will simulate one sail and the sand will simulate reservoir rocks of underground water. As a result seven different models were generated. There were simulated as 1) the anisotropy presence, 2) the rock sail presence, and 3) the injection groove of fluids in the pipeline. The completed models show that the required distance between the unconventional reservoir and underground waters to avoid contamination by fluids is ~200 m, also between the hydraulic fracturing point and the faults that connect with the shallows area is ~350 m, and it is suggested to study in detail the permeability of both: nearby faults and the rock sail. Two Colombian basins (Magdalena Midland Valley and Llanos) were taken as the main base to analyze the assessment of fracking according to the previously mentioned results, concluding that it is viable particularly in areas like Llanos Basin and with some precautions in similar zones to Magdalena Midland Valley Basin.